Digging deeper into decision-making of Chinese long-haul outbound tourists: A two-stage preference-estimation approach - Li, Chunxiao (Spring); McCabe, Scott; Li, Xiang (Robert) (Journal of destination marketing & management, 2017)
A detailed understanding of tourists’ preferences is of great importance both for decision-making theory and destination marketing practice. This study investigates the use of consideration-set formation together with conjoint analysis to estimate the destination preferences of Chinese long-haul outbound tourists. Through the integration of choice-set and characteristic theories, the study demonstrates how to optimise the advantages of both approaches in order to obtain more comprehensive insights into destination choice processes. The findings show that preferences can be analysed effectively in a two-stage model, which can reveal detailed additional insights regarding tourists’ preferences towards destination attributes that cannot be gained through each approach independently, thus contributing to marketing insight on destination choice and selection. •Integrate the theory of consideration-set formation and the characteristic theory.•Explore how evaluation criteria (attributes) are preferred by tourists at the different stages of decision making process.•Uses experimental survey design in the long-haul Chinese outbound market.